The impact of organizational culture on the development of government institutions in Qalqilya governorate - Alaqraa, Nour Taher (Journal of Economic, Administrative and Legal Sciences, 2022)
The aim of the study is to examine the effect of organizational culture on developing governmental institution in Qalqilya district, The researcher adopted the descriptive analytic method to achieve the goal of the study in which a questionnaire was designed, it consisted of (30) items and was distributed on sample of (97) employees who works in governmental institutions in Qalqilya in (2022). The sample was chosen randomly in which the sample represents the population of the study. The results of the study proved that the result regarding the domain of the effect of organizational culture on the effectiveness of performance was high (%97.91) in which there is a positive strong relation between the effect of organizational culture on the effect of performance and the effect of organizational performance on administrative performance in which there is a difference in favor of the effect of cultural organization on developing governmental institutions in Qalqilya district related to gender variable. The study came up with the following recommendations: The importance of considering the importance of organizational culture due to its major effect in developing the institutions and enhancing the effectiveness of administrative and organizational performance through the circulation of organizational culture inside the governmental institutions in addition to the enhancement the organizational culture and to be committed to it particularly the male employees the thing which will be reflected positively on them. Adopting the policy of team spirit among all workers without any exceptions due to the importance of the adoption of such spirit in the development of the administrative and organizational performance.